1994
DOI: 10.1029/94jb00715
|View full text |Cite
|
Sign up to set email alerts
|

Natural controls of fluvial denudation rates in major world drainage basins

Abstract: We present a new compilation of estimates of modern rates of mechanical and chemical denudation for externally drained basins exceeding 5×105 km2 in area. These estimates are based on sediment and solute load data selected in order to represent natural rates as far as possible. Chemical denudation rates have been calculated by deducting the nondenudational component of solute load. Mechanical denudation rates range from 1 mm kyr−1 for the St. Lawrence and Dnepr basins to 670 mm kyr−1 for the Brahmaputra basin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
329
2
6

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 623 publications
(372 citation statements)
references
References 45 publications
17
329
2
6
Order By: Relevance
“…The global study of Meybeck (1976) estimated that dissolved loads were only 20% of the solid fluvial transport load, which we estimate below at 1.8 km 3 /a, implying dissolved transport rates of only around 0.36 km 3 /y. This overall budget has been largely confirmed by more recent studies (Summerfield and Hulton, 1994). More recent studies of weathering of arc crust in the Lesser Antilles Arc argue for lower chemical weathering transport of this type of crust.…”
Section: The Composition Of the Continental Crustsupporting
confidence: 68%
See 1 more Smart Citation
“…The global study of Meybeck (1976) estimated that dissolved loads were only 20% of the solid fluvial transport load, which we estimate below at 1.8 km 3 /a, implying dissolved transport rates of only around 0.36 km 3 /y. This overall budget has been largely confirmed by more recent studies (Summerfield and Hulton, 1994). More recent studies of weathering of arc crust in the Lesser Antilles Arc argue for lower chemical weathering transport of this type of crust.…”
Section: The Composition Of the Continental Crustsupporting
confidence: 68%
“…Studies of rivers in more stable continent regions, such as Siberia (Huh and Edmond, 1999) and even in more tectonized Venezuela (Tosiani et al, 2004) would also support rather lower values of dissolved material flux than suggested by Lee et al (2008). As a result we use a value of 0.4 km 3 /a in our mass balance calculations, following the 20% estimate of Meybeck (1976) and Summerfield and Hulton (1994), while recognizing the uncertainties involved in this.…”
Section: The Composition Of the Continental Crustmentioning
confidence: 99%
“…Analyses of alterites in Equatorial Africa indicate long term evolution from tropical climate during the late Cretaceous and Paleocene, toward more humid equatorial climate during Neogene (Tardy and Roquin, 1998), culminating in the Congo catchment during the Quaternary, with annual precipitation of 1600 mm. Such elevated precipitation rate induces high runoff values (> 40 litres per seconds) that favours mechanical and chemical weathering (Summerfield and Hulton, 1994). Increasing continental erosion throughout the Oligocene to Present is independently documented by the Strontium isotopic ratio: it increases when continental radiogenic granitoids are eroded and transferred to the oceans (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In particular the lower reaches of the Yarlung Tsangpo, Nu, Lancang, Yangtze and Yalong Rivers are characterized by extreme relief at the margins of the QTP. Based upon studies elsewhere (Binnie et al 2007;Harrison 2000;Milliman and Syvitski 1992;Montgomery and Brandon 2002;Summerfield and Hulton 1994), this suggests that landscape attributes such as slope or drainage density dynamically adjust to increased tectonic forcing or impact. These changes could potentially Figure 9 A synthesis of the trunk channel longitudinal profiles and their associated erosion patterns draining the eastern margin of the QTP.…”
Section: Discussionmentioning
confidence: 99%